2005
DOI: 10.1080/13691050500100724
|View full text |Cite
|
Sign up to set email alerts
|

Contextualizing group rape in post‐apartheid South Africa

Abstract: Collective male sexual violence is part of a continuum of sexual coercion in South Africa. This paper is based on long-term ethnographic work in an urban township in the former Transkei region. Drawing on intensive participant observation and interviews with young men in particular, it attempts to make sense of emergent narratives relating to streamlining, a local term for a not uncommon form of collective sexual coercion involving a group of male friends and one or more women. The paper begins with an overvie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(58 citation statements)
references
References 21 publications
(15 reference statements)
3
55
0
Order By: Relevance
“…Male clients may use physical, psychological and sexual violence and humiliation to demonstrate their power to the woman, but more importantly to themselves, to their male peers and other powerful males to whom they may feel inferiorised. Wood's ethnographic work in South Africa describes how group rape or collective sexual coercion (known as "streamlining") is often justified as a means men use to correct the behaviour of girls or women viewed as transgressive or disrespectful to the authority or sexual rights of men [42]. "Streamlining" was used to discipline the woman and humiliate her while reinforcing group bonding through her being "shared" with the man's male friends.…”
Section: Discussionmentioning
confidence: 99%
“…Male clients may use physical, psychological and sexual violence and humiliation to demonstrate their power to the woman, but more importantly to themselves, to their male peers and other powerful males to whom they may feel inferiorised. Wood's ethnographic work in South Africa describes how group rape or collective sexual coercion (known as "streamlining") is often justified as a means men use to correct the behaviour of girls or women viewed as transgressive or disrespectful to the authority or sexual rights of men [42]. "Streamlining" was used to discipline the woman and humiliate her while reinforcing group bonding through her being "shared" with the man's male friends.…”
Section: Discussionmentioning
confidence: 99%
“…This may influence the likelihood of a young person engaging in violence [54], as well as increasing the risk of engaging in other delinquent and criminally violent behaviours, such as alcohol and substance abuse and rape [55]. Activities relating to gangs, guns, and drugs tend to drive increases in the rate of violence within neighbourhoods and the psychological imprint of these experiences expose children to a range of severe negative mental-health outcomes [56].…”
Section: Proximal Societal Factorsmentioning
confidence: 99%
“…9 It's possible that there are inter-provincial differences, but it is also likely that cases where boyfriends are involved are less likely to be reported to the police. This may be due to girlfriends being disinclined to cause harm to their boyfriends or exes, but it is also likely to be related to the risk of reputational damage if a case goes to court.…”
Section: Victim Characteristicsmentioning
confidence: 99%
“…Multiple perpetrator rape is highly stigmatised and victims are often accused of promiscuity and being inebriated. 10 There is substantial under-reporting of all rapes to the police. Research conducted in Gauteng in 2010 found that only one in 25 women interviewed who had been raped had reported it, and only one in 13 of these women reported rapes not involving an intimate partner.…”
Section: Victim Characteristicsmentioning
confidence: 99%